HURTHLE CELL THYROID CARCINOMA (HTC): A RARE INCIDENCE OF BRAIN METASTASIS - Zainol, Muhammad Qyairil Anwar Che; Hamzah, Nabilah Huda; Misron, Nurul Akmar; Ismail, Shartiyah (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Oncocytic or Hurthle cell thyroid carcinoma is a rare type of carcinoma which occurs in 5% of the population with known thyroid carcinoma. Metastasis to the brain is even rarer with 3% of follicular subtypes reported. CASE A 60-year-old female presented with left-sided hemiparesis and slurred speech. She exhibited full consciousness. A cranial CT showed a right frontal lobe intra-axial lesion causing obstructive hydrocephalus. Subsequent MR revealed an enhancing hypointense lesion at the frontoparietal lobe which is suggestive of a glioma. She was referred to the neurosurgical outpatient clinic; however, she experienced a seizure episode and ended up in the emergency department. She was subjected to emergency right craniectomy and tumour excision. Histopathological examination of brain tissue revealed a metastatic carcinoma consistent with a primary thyroid origin. Surveillance CT post-operatively revealed a right thyroid lobe lesion. A biopsy of the right thyroid nodule was performed during the tracheostomy procedure. Histopathological findings were consistent with HTC. A delayed thyroid ultrasound revealed a TIRADS 4 hypoechoic lesion in the right lower pole (1.7 x 2.1 cm). Otherwise, she was clinically and biochemically euthyroid. She underwent whole-brain radiotherapy and was scheduled for total thyroidectomy. CONCLUSION This patient was primarily investigated for glioma, but the histopathology report changed the course of investigation and treatment. Histologically, the oncocytic cell is a follicular “derived” thyroid cell which exhibits abundant granular eosinophilic cytoplasm and is positive for TTF1 and thyroglobulin immunostain. Clinical presentation varies from capsular to vascular and/or distant lymph node invasion, and metastatic spread. In this case, we describe the challenges encountered in diagnosing HTC. Brain metastasis of HTC is rare. The unique presentation as a primary brain tumour with no thyroid nodule or neck swelling delayed the diagnosis. The prognosis of such cases is worse in a high-grade and poorly differentiated disease.